Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/tox.22942
|View full text |Cite
|
Sign up to set email alerts
|

Hyperforin induces apoptosis through extrinsic/intrinsic pathways and inhibits EGFR/ERK/NF‐κB‐mediated anti‐apoptotic potential in glioblastoma

Abstract: Glioblastoma is the most common primary brain tumor with poor survival rate and without effective treatment strategy. Notably, amplification and active mutation of epidermal growth factor receptor (EGFR) occur frequently in glioblastoma patient that may be a potential treatment target. Several studies indicated that various type of herbal compounds not only regulate anti‐depressant effect but also shown capacity to suppress glioblastoma growth via inducing apoptosis and inhibiting oncogene signaling transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…Similar to PI3K-Akt pathway, MEK-ERK signaling has also been considered as a therapeutic target of glioblastoma. Ethyl pyruvate [52], trametinib [53], amentoflavone [54], hyperforin [55], berberine [56], imipramine [57], and protein neddylation inhibitor MLN4924 [58] inhibit glioblastoma cells migration and invasion via suppressing MEK-ERK pathway. Among them, several drugs have been applied in clinical trials such as trametinib (ClinicalTrials.gov Identifier: NCT03363217) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PI3K-Akt pathway, MEK-ERK signaling has also been considered as a therapeutic target of glioblastoma. Ethyl pyruvate [52], trametinib [53], amentoflavone [54], hyperforin [55], berberine [56], imipramine [57], and protein neddylation inhibitor MLN4924 [58] inhibit glioblastoma cells migration and invasion via suppressing MEK-ERK pathway. Among them, several drugs have been applied in clinical trials such as trametinib (ClinicalTrials.gov Identifier: NCT03363217) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Merhi et al showed [ 30 ] a suppression of protein kinase B (AKT) activity in human myeloid cells at HPF concentrations similar to those used in the present work, whereas Hsu et al proved that HPF can inhibit the extracellular signal-regulated kinases (ERK)-1/2 activity in glioblastoma cells [ 56 ]. Regarding pERK1/2 and pAKT, which are both constitutively active in the BRAF-mutated melanoma cell lines, no different expression levels were found at short times (not shown) and after 24 h treatment in A375 and SK-Mel-28 cells ( Figure 6 C).…”
Section: Resultsmentioning
confidence: 64%
“…Similar to PI3K-Akt pathway, ERK signaling has also been considered as a therapeutic target of glioblastoma. Ethyl pyruvate [52], trametinib [53], amento avone [54], hyperforin [55], berberine [56], imipramine [57], and protein neddylation inhibitor MLN4924 [58] inhibit glioblastoma cells migration and invasion via suppressing ERK pathway. Among them, several drugs has been applied in clinical trials such as trametinib (ClinicalTrials.gov Identi er: NCT03363217) [53].…”
Section: Discussionmentioning
confidence: 99%